EFEKTIVITAS PENGGUNAAN MEDIA TEKA-TEKI SILANG DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Nurkusuma, Almira; Achmadi, Achmadi; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The purpose of this research is to know the effectiveness of the application of crossword puzzle in improving students interest. This research was conducted using pre-experimental design with the one-group pretest-posttest design. The subject of this research was seventh grade students of SMP N 9, consisting 30 students. The techniques of data collection are indirect communication techniques and documentary study technique. The tools of data collection in this research were check list to measure the students insterest before treatment and after treatment and note sheet or document. Based on data analysis, the average rates of students interest before treatment is 17, 25 or 58% in moderate category. Whereas from the calculation of learning interest after being treated there was an increase in every aspect so that the average obtained increased by 23 or if the percentage was 77% with a strong category. From the calculation of the effect size obtained a result of 1 with a high category which means the media of learning crossword puzzles has an effect or a big influence in increasing students' interest in learning in social studies subjects VII F SMP Negeri 9 Pontianak. Keywords: Crossword Puzzle, Students Interest, Social Science